New strategies in animal feeding to improve consumer acceptance of animal products - Puchal Mas F.; Mascarell J. (Feed manufacturing in the Mediterranean region: Recent advances in research and technology, 1999)
Animal production is presently going through deep changes from the standpoint of product quality and consumer acceptance of animal products. New fears have been added to the well known sensitivity of consumers, frequently exacerbated by the media, towards the dangers of cholesterol, drug and antibiotic residues, etc., such as salmonella contamination of food and other foodborne diseases possibly transmissible to the consumer, such as the recent outbreaks of BSE or 'mad cow disease', the broiler Hong Kong flu, etc. Both farmers and animal scientists alike should support a strong technological reaction in the sense to guarantee animal products of undoubted quality, free from any type of risks for the consumer. Current day objectives in animal production are presented and experimental results referring to the possible nutritional ways to achieve these goals are reviewed. The role of protein, amino acids and other nutrients, to increase proportion of meat while decreasing fat is discussed.
2. Conference of Feed Manufacturers of the Mediterranean, 1998/03/25-27, Reus (Spain)